Electrical conductivity and positron annihilation characteristics of ternary silicone rubber/carbon black/TiB2 nanocomposites. (December 2015) - Ismail, A.M.; Mahmoud, K.R.; Abd-El Salam, M.H.
Abstract: The effect of TiB2 nano-powder content on the electrical conductivity and positron annihilation characteristics of ternary silicone rubber/CB/TiB2 nanocomposites was studied. The endothermic enthalpy of melting (ΔHm ) and melting temperature of the composites (Tm ) were determined by differential scanning calorimetery (DSC). The addition of 12 phr TiB2 leads to a maximum shift in Tm toward higher temperature. Also, χc values of the investigated composites were found to decrease with increasing TiB2 content. The dc conductivity has reached maxima in the region of 12 phr TiB2 followed by a decrease with increasing TiB2 content. The temperature dependence of the conductivity showed peaks at certain temperatures and shifted to higher temperature with increasing TiB2 content up to 12 phr. Two types of free volume cavities were detected by positron annihilation lifetime, ranging from V1 (8.77–18.18 Å 3 ) and V2 (270.68–274.48 Å 3 ). A correlation between positron annihilation parameters was also used to discuss the properties of the investigated composites.